A Mathematical Model of the Mouse Atrial Myocyte With Inter-Atrial Electrophysiological Heterogeneity - Zhang, Henggui; Zhang, Shanzhuo; Wang, Wei; Wang, Kuanquan; Shen, Weijian (Frontiers in Physiology, 2020)
Biophysically detailed mathematical models of cardiac electrophysiology provide an alternative to experimental approaches for investigating possible ionic mechanisms underlying the genesis of electrical action potentials and their propagation through the heart. The aim of this study was to develop a biophysically detailed mathematical model of the action potentials of mouse atrial myocytes, a popular experimental model for elucidating molecular and cellular mechanisms of arrhythmogenesis. Based on experimental data from isolated murine atrial cells a set of mathematical equations for describing the biophysical properties of membrane ion channel currents, intracellular Ca2+ handling, and Ca2+-calmodulin activated protein kinase II and β-adrenergic signaling pathways were developed. Wherever possible, membrane ion channel currents were modelled using Markov chain formalisms, allowing detailed representation of channel kinetics. The model also considered heterogeneous electrophysiological properties between the left and the right atrial cell. The developed model was validated by its ability to reproduce the characteristics of action potentials and Ca2+ transients, matching quantitatively to experimental data. Using the model, the functional roles of four K+ channel currents in atrial action potential were evaluated by channel block simulations, results of which were quantitatively in agreement with existent experimental data. To conclude, this newly developed model of murine atrial cells provides a powerful tool for investigating possible ion channel mechanisms of atrial electrical activity at the cellular level and can be further used to investigate mechanisms underlying atrial arrhythmogenesis.